2020
DOI: 10.1002/sej.1362
|View full text |Cite
|
Sign up to set email alerts
|

Managing dilemmas of resource mobilization throughjugaad: Amulti‐methodstudy of social enterprises in Indian healthcare

Abstract: Research Summary This study focuses on the dilemmas that social entrepreneurs encounter and the practices used to manage dilemmas over time. Using a multi‐method approach involving event structure analysis and an inductive multiple case study, we find that four key organizational practices—asset multiplication, leveraging human capital, building social embeddedness, and affordable quality—embody the jugaad elements of frugality and inclusivity. Adding to the social entrepreneurship literature, this study demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…The UN General Secretary put together the headings of international development and released the Millennium Development Goals (MDGs) in 2000. In these goals, which were aimed to be achieved by 2015, the headings included the following: to exterminate poverty and hunger (1), to carry into effect primary education at the international level (2), to promote gender equality and empower women (3), to decrease child mortality (4), to strengthen maternal health (5), to fight HIV/AIDS, malaria, and other diseases (6), to ensure environmental sustainability (7), and to develop global cooperation for development (8) [33].…”
Section: Un Sustainable Development Goals (Sdgs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The UN General Secretary put together the headings of international development and released the Millennium Development Goals (MDGs) in 2000. In these goals, which were aimed to be achieved by 2015, the headings included the following: to exterminate poverty and hunger (1), to carry into effect primary education at the international level (2), to promote gender equality and empower women (3), to decrease child mortality (4), to strengthen maternal health (5), to fight HIV/AIDS, malaria, and other diseases (6), to ensure environmental sustainability (7), and to develop global cooperation for development (8) [33].…”
Section: Un Sustainable Development Goals (Sdgs)mentioning
confidence: 99%
“…Today, it is possible to divide entrepreneurship into many subtypes. It can be observed that the structure established by entrepreneurs can fit into more than one subtype of entrepreneurship [7]. While there are entrepreneurs whose aim is to generate profit, there are also entrepreneurs who do not aim to gain a profit.…”
Section: Introductionmentioning
confidence: 99%
“…Then there are social business models which focus on the achievement of social goals for market participants [21] and the base of pyramid business models that aim to alleviate poverty and increase profitability through radical innovations that cater to the needs of poor and vulnerable communities [2]. Examples of radical innovations include resource-constrained frugal, costs-based or good enough innovation aimed at producing affordable products for low-income consumers [22][23][24][25][26][27][28][29]. However, Sharmelly and Ray [22] also point out the challenges of economic sustenance (financial gains) for firms producing low cost and affordable products for subsistence consumers.…”
Section: Sustainable Business Model Innovationmentioning
confidence: 99%
“…Because the market logic is less likely to be dominant in these situations, negotiators are more likely to prioritize noneconomic issues, allowing greater opportunity for creative solutions unconnected to past practice. Notably, according to Foo, Vissa, and Wu (2020), entrepreneurs in emerging economies are more likely to rely on nonmarket logics, which is reflected in frugal resource mobilization activities (Agarwal et al 2020).…”
Section: The Continuum Of Entrepreneurial Negotiationmentioning
confidence: 99%